2017
DOI: 10.1007/s40615-017-0409-2
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparity in the Perioperative Care for Patients Undergoing Total Knee and Hip Arthroplasty: A Retrospective Propensity-Matched Cohort Study

Abstract: There is no significant difference in the type of anesthesia received for total joint arthroplasty between African-American and White patients; however, there is a disparity in the postoperative outcomes in favor of the White patient group. Further studies needed to explain the reasons for these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Elsharydah et al found that a propensity matched cohort of black patients had higher rates of 30 day complications for lower extremity arthroplasty. 10 Several studies have found that hospital factors such as safety net burden impact surgical outcomes. [31][32][33][34][35] Hoehn et al 21 reported that high safety net burden hospitals had higher postsurgical mortality and LOS; subgroup analysis of THA patients found increased costs with procedures performed at high burden hospitals but no mortality or readmissions difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elsharydah et al found that a propensity matched cohort of black patients had higher rates of 30 day complications for lower extremity arthroplasty. 10 Several studies have found that hospital factors such as safety net burden impact surgical outcomes. [31][32][33][34][35] Hoehn et al 21 reported that high safety net burden hospitals had higher postsurgical mortality and LOS; subgroup analysis of THA patients found increased costs with procedures performed at high burden hospitals but no mortality or readmissions difference.…”
Section: Discussionmentioning
confidence: 99%
“…6 Evidence supports the association between THA outcomes and multifactorial patient-level, provider-level and hospital-level racial and socioeconomic disparities. [7][8][9][10][11][12][13][14][15][16] Hospital safety net burden is defined as the proportion of cases at an individual hospital with the primary insurance payer being Medicaid or uninsured; safety net hospitals operate with a mandate or adopted mission to deliver care to patients regardless of their ability to pay. 17 18 Research shows higher rates of mortality, hospitalacquired infection, perioperative complications and poorer markers of surgical quality (timeliness, patient centeredness and equity of treatment) at high safety net burden hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of co-morbidities that can affect the outcomes, diabetes is worrying, given the comprehensive literature linking diabetes to elevated complication rates in TJA patients [35][36][37][38]. Racial inequalities are multifactorial, with patient, provider, and device variables as contributing factors [39]. Many of these contributing factors are possibly modifiable, but further research is required to pinpoint them.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, not all studies have demonstrated an association between patient ethnicity and the use of neuraxial analgesia. For example, in a retrospective propensity-matched study of adults undergoing knee and hip replacement surgery, ethnic-based differences in the use of neuraxial analgesia were not observed after controlling for several important demographic and clinical factors (Elsharydah et al, 2018). This raises the possibility that in patient groups with relatively similar preoperative characteristics, such as ours, the association between the use of epidural analgesia and patient ethnicity may be less significant.…”
Section: Discussionmentioning
confidence: 99%